OTHR-08. Efficacy of anti-epileptic drug prophylaxis on seizure prevention in patients with brain metastases: A systematic review and meta-analysis. (9th August 2021) - Souders, Leslie; Beg, Usman; Svetly, Conner; Dabrowski, Michael; Hamidi, Nima; Padmanaban, Varun; Mansouri, Alireza
Abstract: Introduction: Seizures can occur in patients with brain metastasis and are often debilitating, leading to morbidity, mortality, and economic burden. Implementation of anti-epileptic drugs (AEDs) prophylaxis remains controversial, and provider dependent as current Level III guidelines recommend against their use. This systematic review gathers the current evidence on the effectiveness of AED prophylaxis on preventing new-onset seizures in patients with BM. Associated adverse effects of AED usage in this population are also reported. Methods: Using PRISMA guidelines, a pertinent search was conducted on Embase, PubMed, and Web of Science to identify journal articles that reported AED prophylaxis as a variable to modify seizure frequency in adult patients with BM. Data of interest included AED agent, new-onset seizure frequency, and safety profile. A meta-analysis was performed to calculate odds ratio using Der-Simonian and Laird methods to compare AED group with control for new seizures. Heterogeneity was determined by Cochran Q test and I2. Results: Our search returned 175 publications of which 5 retrospective cohort studies met inclusion criteria. A total of 1, 292 patients (283 receiving AED prophylaxis, and 1, 009 in control group) were included across the studies. AEDs used were phenobarbital, levetiracetam, phenytoin, and valproate. Meta-analysis showed no difference in seizure frequency between the AED and the control group (OR = 0.98; 95%-CI: 0.56–1.72). Heterogeneity: I 2 = 7%. Adverse events were not reported in the publications. Conclusion: Our meta-analysis suggests that there is no improvement in frequency of new seizures with AED prophylaxis in BM patients, supporting current guidelines. However, the evidence is based on a small patient population and retrospective studies. Additional studies are needed to determine efficacy of prophylaxis with newer AEDs and establish guidelines to target therapies for improving morbidity, mortality, and quality of life in patients with BM.